2016
DOI: 10.1016/j.amepre.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The First National Study of Neighborhood Parks

Abstract: Introduction An extensive infrastructure of neighborhood parks supports leisure time physical activity in most U.S. cities; yet, most Americans do not meet national guidelines for physical activity. Neighborhood parks have never been assessed nationally to identify their role in physical activity. Methods Using a stratified multistage sampling strategy, a representative sample of 174 neighborhood parks in 25 major cities (population >100,000) across the U.S. was selected. Park use, park-based physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
165
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(178 citation statements)
references
References 26 publications
8
165
3
2
Order By: Relevance
“…al. 30 , did not find differences between socioeconomic level and accessibility. However, Vieira et al 12 found significant positive association between the level of social development of a neighborhood and quality of parks for physical activity in Rio de Janeiro, Brazil.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…al. 30 , did not find differences between socioeconomic level and accessibility. However, Vieira et al 12 found significant positive association between the level of social development of a neighborhood and quality of parks for physical activity in Rio de Janeiro, Brazil.…”
mentioning
confidence: 79%
“…20 verified inverse relationship between population density and number of available spaces for physical activity. The population density around the parks may represent potential users, so it is necessary to generate public policy to improve the quality conditions of parks and establish strategies to motive the active use of those parks 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations